Multimodal Substitutes in Public Transport: Efficient Variety or Wasteful Competition?. (1st January 2022) - Hörcher, Daniel; Graham, Daniel
The question we raise is whether it is desirable under public ownership to run multiple public transport services (for instance, buses and trains) along a transport corridor, when these modes are (imperfect) substitutes. The paper applies the theory of product differentiation in the context of welfare oriented public transport provision. We react to ongoing policy debates by showing that modal variety may well be beneficial for society, if the spread of consumer preferences is sufficiently wide and the magnitude of scale economies in service provision is limited. This point is supported by theory and illustrated with an agent-based simulation model.